2017
DOI: 10.1177/0020764017700174
|View full text |Cite
|
Sign up to set email alerts
|

High burden of mental illness and low utilization of care among school-going youth in Central Haiti: A window into the youth mental health treatment gap in a low-income country

Abstract: Background The mental health treatment gap for youth in low- and middle-income countries (LMICs) is substantial; strategies for redress are urgently needed to mitigate the serious health and social consequences of untreated mental illness in youth. Aims To estimate the burden of major depressive episode (MDE) and posttraumatic stress disorder (PTSD) as well as utilization of care among Haitian youth in order to describe the mental health treatment gap in a LMIC setting. Methods We estimated the point preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Following their ZL clinical assessment, 53 and 32 students, respectively, warranted a recommendation that follow-up mental health care or psychosocial support could be helpful; thus, 70.8% of students ( n =85) had an identified mental health need. In addition, we have previously reported that 36.7% of student participants were assigned a diagnosis of MDE, PTSD, or a subthreshold variant by research interview (Eustache et al, 2017b). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following their ZL clinical assessment, 53 and 32 students, respectively, warranted a recommendation that follow-up mental health care or psychosocial support could be helpful; thus, 70.8% of students ( n =85) had an identified mental health need. In addition, we have previously reported that 36.7% of student participants were assigned a diagnosis of MDE, PTSD, or a subthreshold variant by research interview (Eustache et al, 2017b). …”
Section: Resultsmentioning
confidence: 99%
“…Baseline psychosocial assessments developed or adapted for the study, including a diagnostic interview, are described in detail elsewhere (Eustache et al, 2017b). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Available evidence from Haiti supports a high prevalence of depression, PTSD, and suicidal ideation [15][16][17]; emotional distress related to violence and life stressors [18][19][20]; and exposure to traumatic events related to the 2010 earthquake [21][22][23]. Emotional distress and mental illness are frequently communicated through idioms of distress; patients and families often pursue religious and traditional healing resources for mental illness [24,25].…”
Section: Introductionmentioning
confidence: 99%